(3QSGdI aj CNHGQ GdChdjGAs - (3Uaj GdOjf CHh YHO Gddg GdMSjf Hf Ydj GHf XGaQ GdGROj, GHf XGaQ GdGROj,J (B657 (3g` s
(3ChdgG (B:s
(3SCdfj hdOj EHQGgje Cf CLeY dg TjFkG ef CNHGQ GdChdjGA GdPjf QCjJge , aGSJNQJ Gddg JYGdi , hcGf gPG hbO HdZJ ef GdYeQ CQHYkG hKeGfjf SfI s
(3BNQgG (B:s
(3BNQ eGhLOJg ef cdGe SjOi GdTjN Uaj GdOjf hGdMeO ddg ChdkG hBNQ s
(3hgj JTJed Ydi efGbH TjNg CHj GdYHGS GdJLjHjs
(3hYHOGdQMje GdbfGhj hCHj GdfLG SGde hZjQges
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B554 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B196 s
Keywords: (3GdJGQjNs